A Standardized Mobile Phone Test on University Students in the City of Arequipa, Peru - Gamero, Katherine (2016)
The objective of this study is to determine validity and reliability of the Mobile Phone Dependency Test (CPDT), in a 22 items Likert scale-based instrument. The Test was administered to two samples, a public university (N=1044) and a private university (N=356) in the Peruvian city of Arequipa. Validity was determined using an exploratory factor analysis. Three factors were identified: abstinence and tolerance (α=0,901), abuse and problems with impulse control (α=0,853), and problems with excessive mobile phone use (α=0,853). Additionally, percentile ranks were created for both public and private universities.